P328 In silico evaluation and pre-clinical efficacy of anti-TNF and anti-IL-23 combination therapy in Inflammatory Bowel Disease. (21st January 2022) - Perrigoue, J; Muniz-Bongers, L; Ong, L; Chen, Y; Chang, L; Ngo, K; Stojmirovic, A; O'Brien, C; Germinaro, M; Rao, R; Vetter, M; Towne, J
Abstract: Background: Despite advances in the treatment of inflammatory bowel diseases (IBD), fewer than, 40% of patients reach clinical remission, suggesting that improved response rates may require targeting of multiple pathogenic pathways through combination therapy. However, the rational selection of combination therapies based on patient and pre-clinical data remains a significant challenge. Methods: Here, we used Crohn's disease (CD) patient-derived molecular networks as a platform for bridging pre-clinical animal models of combination therapy to human disease. Intestinal transcriptional signatures of anti-TNF, anti-IL-23 or combination treatments were generated from the anti-CD40 agonistic antibody murine colitis model and the murine genes mapped to their human orthologues. Humanized gene signatures were intersected with human disease networks to generate treatment subnetworks and enrichment analyses performed. Results: The anti-TNF subnetwork was enriched in genes expressed in myeloid cells, chemokine signaling and NFkB signaling, while the anti-IL-23 subnetwork was enriched in genes expressed in the intestinal epithelium, IL-17 signaling, and cell adhesion. The intersection of these two therapeutic gene signature subnetworks was significantly enriched in IBD GWAS loci genes and human CD inflammatory gene signatures, suggesting that the molecular mechanisms reflected in the pre-clinical model faithfully captures aspects of the human disease. Simultaneous inhibition of these two pathways could result in enhanced efficacy through targeting shared inflammatory pathways and complementary biology in myeloid and epithelial cells to reduce colitis. To test this hypothesis, mice were treated with varying doses of anti-IL-23, anti-TNF, or the combination of both. A synergistic response to combination therapy was observed both in reduction of systemic weight loss and inhibition of local colonic tissue inflammation by histopathology. A set of genes uniquely significantly modulated by the combination therapy compared to either monotherapy was mapped to our human IBD network. Upregulated gene networks in the combination therapy enriched in stromal cells, epithelial mesenchymal transition and extracellular matrix pathways, and adhesion pathways while downregulated gene networks were enriched in IBD disease signatures, M1 macrophages, neutrophils and IFN-γ signaling. Conclusion: These results provide a novel, data-driven approach to predict effective combination therapies for inflammatory diseases and suggest that anti-TNF and anti-IL-23 combination therapy may drive more patients into deep remission through impacts on both shared and unique molecular pathways involved in IBD pathogenesis.